2013
DOI: 10.1371/journal.pone.0051701
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 Mediates MMP9 Expression in Lung Epithelial Cells

Abstract: The purposes were to study the role of lipopolysaccharide (LPS)-induced tumor necrosis factor (TNF)-α/nuclear factor-κB (NF-κB) signaling in matrix metalloproteinase 9 (MMP9) expression in A549 cells and to investigate the effects of lentivirus-mediated RNAi targeting of the disintegrin and metalloproteinase 17 (ADAM17) gene on LPS-induced MMP9 expression. MMP9 expression induced by LPS in A549 cells was significantly increased in a dose- and time-dependent manner (p<0.05). Pyrrolidine dithiocarbamate (PDTC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…28 To evoke inflammatory responses in the RTE cells, we used LPS at a concentration of 0.1 mg/mL which was previously shown to induce MMP9 mRNA expression through the NF-kB pathway in A549 lung epithelial cells. 29 A role of MMP-9 in the development of inflammation is also well established as an inflammatory marker. 30,31 To determine whether rCC16 plays an anti-inflammation Figure 2, increased expression of MMP-9 was observed on both mRNA (Figure 2(a)) and protein levels (Figure 2(b)) in LPS-treated RTE cells, and these LPS-stimulated MMP-9 expressions were inhibited by rCC16 in a dose-dependent manner, being significant at concentrations over 1.0 mg/mL.…”
Section: Rcc16 Inhibits Lps-induced Mmp-9 Expression In Rte Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 To evoke inflammatory responses in the RTE cells, we used LPS at a concentration of 0.1 mg/mL which was previously shown to induce MMP9 mRNA expression through the NF-kB pathway in A549 lung epithelial cells. 29 A role of MMP-9 in the development of inflammation is also well established as an inflammatory marker. 30,31 To determine whether rCC16 plays an anti-inflammation Figure 2, increased expression of MMP-9 was observed on both mRNA (Figure 2(a)) and protein levels (Figure 2(b)) in LPS-treated RTE cells, and these LPS-stimulated MMP-9 expressions were inhibited by rCC16 in a dose-dependent manner, being significant at concentrations over 1.0 mg/mL.…”
Section: Rcc16 Inhibits Lps-induced Mmp-9 Expression In Rte Cellsmentioning
confidence: 99%
“…The results showed that PDTC significantly inhibited LPS-evoked MMP9 protein expression (supplemental Figure 3), as previously determined under similar conditions in the lung epithelial cells. 29 We next performed dual luciferase reporter assays to assess whether suppression of MMP-9 by rCC16 in LPS-stimulated RTE cells is dependent on NF-kB-mediated transcriptional activation. As shown in Figure 3(a), LPS caused an approximate ninefold increase in relative luciferase activity, and rCC16 inhibited LPS-induced NF-kB transcriptional activity in a concentration-dependent manner, from 38.8% at 1.0 mg/ mL to 62.6% reduction at 2.0 mg/mL.…”
Section: Rcc16 Inhibits Lps-induced Mmp-9 Expression In Rte Cellsmentioning
confidence: 99%
“…TNF-α induces the NF-κB signaling pathway to mediate the matrix metalloproteinase-9 (MMP-9) expression (25,26). Findings of a recent study showed that ADAM17 can mediate MMP-9 expression in lung epithelial cells (27). Therefore, we hypothesized that miR-145 is able to inhibit the HCC cell growth by moderating the ADAM17/MMP-9 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The human ADAM17 mRNA sequence (GenBank accession number: NM_003183) was used to determine suitable siRNA target sequences and CCTATGTCGATGCTGAACAAA was selected. The recombinant pLVTHM vectors were constructed by Sangon Biotech Co., Ltd. (Shanghai, China) as the previous study . The orientation of the inserted shRNA cassettes was verified by restriction enzyme analysis and DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant pLVTHM vectors were constructed by Sangon Biotech Co., Ltd. (Shanghai, China) as the previous study. 18 The orientation of the inserted shRNA cassettes was verified by restriction enzyme analysis and DNA sequencing. A negative control (NC) siRNA sequence (TTCTCCGAACGTGTCACGT) was used as a control for ADAM17 siRNA.The recombinant pLVTHM vectors and packaging helper plasmids were co-transfected into 293T cells (Shanghai Institute of Biology, Chinese Academy of Sciences, China) with calcium phosphate.…”
Section: Lentivirus Production and Transductionmentioning
confidence: 99%